Identification of non plastidic adp-glucose pyrophosphorylase unconventional partners in Arabidopsis thaliana - Vinh, Pham Ngoc; Nam, Hong Gil; Hoang, Nguyen Huy (Academia Journal of Biology, 2015)
ADP-glucose pyrophosphorylase (ATP: alpha-glucose-1-phosphate adenylyl transferase, ADGase) previously has been studied as a key regulatory enzyme in the starch biosynthetic pathway in plant. Surprisingly, ADP-glucose pyrophosphorylase small subunit APS1 (ADG1) was found not only in chloroplast but also in non plastidic region, especially, small proportion in nucleus. To elucidate the novel mechanisms underlying non plastidic ADG1 actions, yeast two-hybrid screening method was used to identify proteins associated with ADG1. Yeast two hybrid assay and co-immunoprecipitation (Co-IP) assay were used to confirm the interaction between ADG1 and interacting candidates. Furthermore, localization of interacting proteins was analyzed using Green Fluorescent Protein (GFP) fusion proteins under laser scanning microscopy. Two protein RPC4 (RNA polymerase III subunit) and LSU3 (Response to low Sulfur 3) were confirmed as strong candidates which interact with ADG1. Therefore, we hypothesized that non plastidic localized-ADG1 might have additional function which mediate plant cellular metabolism status and intracellular signaling to regulate proper plant growth and development.